Comparing Umbilical Cord Management Strategies in Nonvigorous Newborns: A Systematic Review and Network Meta-analysis - Aldemerdash, Mohamed A.; Abdellatif, Mohammed; Refaey, Doha; AbuSammour, Yaser; Refaey, Mahmoud; Janem, Abdelrhman Muwafaq; Hasan, Mohammed Tarek; Aldemerdash, Ahmed; Shihab, Huda; Hamouda, Naema (American Journal of Perinatology, 2025)
Nonvigorous newborns often require immediate resuscitation, and early cord clamping (ECC) is the conventional approach. Alternative strategies, such as intact cord resuscitation (ICR) and umbilical cord milking (UCM), may provide additional benefits without compromising safety. To compare the effectiveness and safety of different umbilical cord management strategies for nonvigorous newborns. We followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines and searched six databases for randomized controlled trials comparing different umbilical cord management approaches in nonvigorous newborns. Outcomes assessed included resuscitation effectiveness, hematological parameters, neonatal morbidities, and mortality. The Cochrane Collaboration tool RoB2 was used to assess the risk of bias. Ten studies with 2,541 newborns were included, with seven studies contributing to the meta-analysis. No significant differences were observed in resuscitation requirements, Apgar scores, or mortality between ECC, ICR, and UCM. However, at 5 minutes, ICR showed a small but statistically significant higher Apgar score compared with other interventions (mean difference [MD] = 0.3, 95% confidence interval [CI] [0.05, 0.55]). Additionally, heart rate was lower in the intact ICM (I-UCM) group (MD = −34.75 beats/min, 95% CI [−61.84, −7.66]). Cut UCM was associated with significantly higher serum ferritin levels at 6 weeks (MD = 40.44 µg/L, 95% CI [26.45, 54.43]). Initial hematocrit levels were also higher in the ICR group compared with ECC. ICR and UCM might be safe and effective alternatives to ECC for nonvigorous newborns, with potential hematological benefits. However, further large-scale studies are needed to confirm these findings and evaluate long-term neurodevelopmental outcomes.
Keywords: nonvigorous newborns; umbilical cord management; intact cord resuscitation; umbilical cord milking; early cord clamping